Nuclear Medicine in Diagnosis of Prosthetic Valve Endocarditis: An Update. (28th January 2015) - Musso, Maria; Petrosillo, Nicola
Abstract : Over the past decades cardiovascular disease management has been substantially improved by the increasing introduction of medical devices as prosthetic valves. The yearly rate of infective endocarditis (IE) in patient with a prosthetic valve is approximately 3 cases per 1, 000 patients. The fatality rate of prosthetic valve endocarditis (PVE) remains stable over the years, in part due to the aging of the population. The diagnostic value of echocardiography in diagnosis is operator-dependent and its sensitivity can decrease in presence of intracardiac devices and valvular prosthesis. The modified Duke criteria are considered the gold standard for diagnosing IE; their sensibility is 80%, but in clinical practice their diagnostic accuracy in PVE is lower, resulting inconclusively in nearly 30% of cases. In the last years, these new imaging modalities have gained an increasing attention because they make it possible to diagnose an IE earlier than the structural alterations occurring. Several studies have been conducted in order to assess the diagnostic accuracy of various nuclear medicine techniques in diagnosis of PVE. We performed a review of the literature to assess the available evidence on the role of nuclear medicine techniques in the diagnosis of PVE.